Surgical Endodontics vs Regenerative Periodontal Surgery for Management of a Large Periradicular Lesion - Asgary, Saeed; Roghanizadeh, Leyla; Haeri, Ali (Iranian Endodontic Journal, 2018)
Treatment success of periodontal-endodontic lesions is dependent on the elimination of both disease causative factors, whether they exist separately or concurrently. This report presents successful endodontic management of a misdiagnosed large periradicular pathology, which had not resolved after a previous periodontal regenerative surgery. A patient complaining of discomfort in the left maxillary region was referred. He had undergone regenerative surgery for treatment of a large periradicular defect; however, there was no further amelioration of the clinical signs/symptoms. Radiographically, a large periradicular lesion filled with bone substitute materials was detected around tooth #25. The endodontic treatment of the tooth was imperfect; therefore, surgical endodontic retreatment was planned. During root-end surgery, the biopsy containing bone substitute materials was obtained. Root-end filling/sealing using calcium-enriched mixture cement was completed. The histopathological examination showed granulation tissues enclosing exogenous materials. In two-year radiographic evaluation, resolving lesion and complete bone healing was observed. The first fundamental step in the management of periradicular lesions is correct diagnosis of the lesion origin and set-by step of the treatment plan according to the main causative factor. Regenerative periodonttal surgery, without considering the defective apical seal, will only cause a painful procedure for the patient without any positive benefit. Following appropriate apical seal, the endodontic lesion healing can be anticipated. Keywords: Apical Periodontitis; Apical Seal; Calcium-Enriched Mixture; CEM Cement; Diagnostic Errors; Endodontic-Periodontal Lesions; Endodontic Surgery